46th AIAA Fluid Dynamics Conference 2016
DOI: 10.2514/6.2016-3940
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the DNS Data Averaging Time on the Accuracy of RANS-DNS Simulations

Abstract: Statistical data obtained from direct numerical simulations (DNS) are often used as reference data for validating turbulence models. Thus, accuracy of the DNS data itself is of particular importance for understanding the potential error in Reynolds-averaged Navier- Stokes (RANS) simulations. Recent studies demonstrate that when the DNS data is used to represent budget terms in the RANS equations, simulations of wall-bounded turbulent flows conducted with such equations (herein referred to as RANS-DNS simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Higher-order statistics were not collected in [21], but as has already been mentioned above, their statistical convergence was found acceptable in [14] using standard approaches to the statistical error estimation. As for the systematic error discovered in [21] in the second-order statistics, it is unlikely to expect higher-order statistics to be free from this error. Moreover, one would expect such error to be larger in odd moments as they are sensitive to the direction of velocity fluctuations in contrast to even moments.…”
Section: Analysis Of Discrepancy Between the Model And Dns Profilesmentioning
confidence: 94%
See 3 more Smart Citations
“…Higher-order statistics were not collected in [21], but as has already been mentioned above, their statistical convergence was found acceptable in [14] using standard approaches to the statistical error estimation. As for the systematic error discovered in [21] in the second-order statistics, it is unlikely to expect higher-order statistics to be free from this error. Moreover, one would expect such error to be larger in odd moments as they are sensitive to the direction of velocity fluctuations in contrast to even moments.…”
Section: Analysis Of Discrepancy Between the Model And Dns Profilesmentioning
confidence: 94%
“…However, convergence of statistics including highorder moments was tested, discussed at length and found adequate in [14]. In addition, the same DNS in the unstrained channel were run about ten times longer in our separate study [21]. In [21],…”
Section: Analysis Of Discrepancy Between the Model And Dns Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…When RANS-DNS simulations were conducted in planar wall-bounded turbulent flows such as a channel flow and a zero-pressure gradient boundary layer over a flat plate using DNS data from [9][10][11], it was found that errors in such data were significant for their use in such simulations. The following work [12] demonstrated that statistical errors are unlikely to be the leading source of uncertainties in DNS data. That is, uncertainties in numerical procedures used in DNS have to be explored further, with the grid resolution near a wall raising questions in particular.…”
Section: Introductionmentioning
confidence: 90%